SIMULATION TECHNOLOGIES IN THE MODELLING USERS’ BEHAVIORS IN THE PHARMACEUTICAL MARKET - Соколовська, З. М.; Капустян, І. В. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2019)
The creation of a new branch of economics – behavioural economics studying the features of decision-making, resulted in changes of a number of fundamental ideas. The modern view of the economy, as a complex adaptive system, makes it necessary to use new methodologies for modeling dynamic processes, events arising over time, reproduce and transform.The apparatus of simulation modeling based on three main paradigms - Discrete Event, System Dynamics, and Agent Based - and their combinations meets these requirements Modeling the ‘arising’ behaviour of economic agents and developing forecasting models of commodity markets became possible with the advent of behavioural economics and simulation technologies. The domestic pharmaceutical market is one of the most dynamic, flexible and highly competitive, and the pharmaceutical industry is one of the active and gradually growing sectors of the Ukrainian economy. The need for taking into consideration its relationship to healthcare (with a significant range of specific agents), the active implementation of information and communication technologies, the emergence of a new type of users with complicated behaviour and a dynamic change in the preferences determines the relevance of conducting a special research of the pharmaceutical market. At the same time, application of such flexible tools as simulation technologies is gaining particular importance. The objective of this article is the reveal the possibilities of using simulation technologies in modeling the user’s behaviour in the pharmaceutical market. The article presents the results of the experiments conducted on the simulation models of consumer behavior of original and generic medicines in terms of working out their sales promotion strategies. The models are developed using the multi-level simulation paradigm (a combination of Agent-Based and System Dynamics approaches) on the platform of the AnyLogic system. In the experiments, materials from leading pharmaceutical companies of Ukraine were used. The experiments have proved the possibility to reproduce the consumers’ behaviour in dynamics, taking into account the influence of numerous stochastic factors in the market environment. Models are offered for use in the process of making managerial decisions on the production and sales of products by pharmaceutical enterprises. Models can be tailored to the specifics of a particular enterprise.